2021
DOI: 10.1513/annalsats.202008-940oc
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine versus Azithromycin for Hospitalized Patients with COVID-19. Results of a Randomized, Active Comparator Trial

Abstract: Rationale: The coronavirus disease (COVID-19) pandemic struck an immunologically naive, globally interconnected population. In the face of a new infectious agent causing acute respiratory failure for which there were no known effective therapies, rapid, often pragmatic trials were necessary to evaluate potential treatments, frequently starting with medications that are already marketed for other indications. Early in the pandemic, hydroxychloroquine and azithromycin were two such candidates. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 35 publications
1
35
0
Order By: Relevance
“…Characteristics of participants assigned to azithromycin and to standard care were similar (table 1; appendix pp [12][13][14][15][16][17][18][19][20][21][22]. The mean participant age was 45•9 years (SD 14•9); 152 (52%) of 295 were men and 143 (49%) were women; 201 (68%) were White, 47 (16%) were Asian or Asian British, 11 (4%) were Black or Black British, and 36 (12%) were Mixed or other race; 70 (24%) participants had comorbidities; and the median duration of symptoms before enrolment was 6•02 days (3•52).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristics of participants assigned to azithromycin and to standard care were similar (table 1; appendix pp [12][13][14][15][16][17][18][19][20][21][22]. The mean participant age was 45•9 years (SD 14•9); 152 (52%) of 295 were men and 143 (49%) were women; 201 (68%) were White, 47 (16%) were Asian or Asian British, 11 (4%) were Black or Black British, and 36 (12%) were Mixed or other race; 70 (24%) participants had comorbidities; and the median duration of symptoms before enrolment was 6•02 days (3•52).…”
Section: Resultsmentioning
confidence: 99%
“…12 Despite these theoretical considerations, large-scale clinical trials of azithromycin either alone or coadministered with hydroxychloroquine have not shown clinical efficacy in reducing mortality, need for invasive mechanical ventilation, duration of hospital admission, or clinical status on ordinal outcome scores in patients admitted to hospital with COVID-19. [13][14][15][16] However, these trials were all done in late-stage, severe disease with 17-40% mortality. They did not study patients at earlier stages of disease in the community and are not able to make conclusions about the effectiveness of azithromycin outside the hospital setting.…”
Section: Introductionmentioning
confidence: 99%
“…Gautret et al [31] were the first to highlight the effectiveness of dual therapy, showing better results with HCQ + AZM than with HCQ alone, under rigorous cardiological surveillance, in reducing hospitalisation and mortality. Many other studies concluded that given the efficacy of HCQ + AZM in early outpatient treatment, the evidence on the use of HCQ alone or HCQ + AZM in inpatients is irrelevant to its use in high-risk outpatients in early stages of the disease [32, 33]. In addition, triple therapy with HCQ + AZM + Zn improved the outcomes and reduced the duration of hospitalisation [34].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 74 studies 2, 5, 15-18, 36-39, 41-44, 47-54, 56, 57, 59-63, 65-67, 69, 70, 72, 74-76, 78, 79, 82, 83, 85, 87, 88, 90-92, 94-97, 99, 100, 103-121, 125 including 48622 patients reported all-cause mortality. After filtering out treatments with small sample size following the specified criteria, the network included azithromycin, hydroxychloroquine, hydroxychloroquine plus azithromycin, colchicine, arbidol (umifenovir), favipiravir, remdesivir, lopinavir/ritonavir, convalescent plasma, methylprednisolone, dexamethasone, hydrocortisone, immunoglobulin, interferon beta, recombinant human granulocyte colony-stimulating factor (GCSF), tocilizumab, vitamin D 3 , baricitinib plus remdesivir, sulodexide and SOC.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 48 studies reported the number of patients required for MV during the study period. 2, 5, 15-17, 36-39, 41-44, 47-50, 56, 57, 60-63, 65, 69, 72, 76, 78, 82, 83, 87, 92, 95-97, 100, 103-105, 108-110, 112-114, 116, 117, 120 with 41405 patients and 4455 events. We included azithromycin, hydroxychloroquine, hydroxychloroquine plus azithromycin, remdesivir, lopinavir/ritonavir, convalescent plasma, methylprednisolone, dexamethasone, hydrocortisone, immunoglobulin, interferon beta, recombinant human GCSF, tocilizumab, vitamin D 3 , baricitinib plus remdesivir, sulodexide and SOC as treatment nodes in the NMA.…”
Section: Resultsmentioning
confidence: 99%